hubungan POLA ASUH ORANG TUA DAN CHILD FEEDING DENGAN KEJADIAN PICKY EATER PADA ANAK USIA TODDLER (1-3 TAHUN) - Sya’diyah, Nanda Halimatus; Maghfuroh, Lilis; Aisyah, Harnina Samantha (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Picky eating is a selective and limited eating behavior problem in toddlers, namely only wanting to eat certain types of food and refusing other foods.Children with picky eating often have difficulty consuming balanced and nutritious foods, which can affect their nutritional status and health. Factors that influence picky eating include maternal employment status, parenting patterns, child feeding, and parity. The purpose of this study was to analyze the relationship between parenting patterns and child feeding with the incidence of picky eating in toddlers (1-3 years).This study used an analytical design with a cross-sectional approach.The study population was 183 respondents, with a sample size of 125 respondents selected through a simple random sampling technique. The research instrument used a questionnaire. Data analysis was carried out using the Spearman rho statistical test in SPSS 27.0. The results of this study indicate that (32.0%) parents with permissive parenting styles have picky eater children, significant value p value = 0.03 (P <0.05) there is a relationship between parenting styles and the incidence of picky eaters as many as (80.8%) with inappropriate child feeding, significant value p value = 0.03 (P <0.05) there is a relationship between child feeding and the incidence of picky eaters.